2002
DOI: 10.1109/tps.2002.805418
|View full text |Cite
|
Sign up to set email alerts
|

Instability growth in magnetically imploded high-conductivity cylindrical liners with material strength

Abstract: Magnetically imploded cylindrical metal shells ( -pinch liners) are attractive drivers for experiments exploring hydrodynamics and properties of materials at extreme conditions. As in all -pinches, the outer surface of a liner is unstable to magneto Rayleigh-Taylor (RT) modes during acceleration, and large-scale distortion arising from RT modes could make such liners unuseable. On the other hand, material strength in the liner should, from first principles, reduce the growth rate of RT modes, and material stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 12 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…The remaining published controlled studies of MRT growth were PHYSICS OF PLASMAS 18, 056301 (2011) done on multimicrosecond generators in which the imploding liners have significant material strength and remain in liquid or solid states for much of the implosion. 12 By contrast, in fast ($100 ns) implosions strong shocks can develop in the liner and the liner is typically in the plasma state for much of the implosion. Due to the lack of high-quality data for the submicrosecond regime, the magnetohydrodynamics physics packages of simulation codes (e.g., LASNEX, 13 HYDRA, 14 GORGON 15 ) are not well validated.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining published controlled studies of MRT growth were PHYSICS OF PLASMAS 18, 056301 (2011) done on multimicrosecond generators in which the imploding liners have significant material strength and remain in liquid or solid states for much of the implosion. 12 By contrast, in fast ($100 ns) implosions strong shocks can develop in the liner and the liner is typically in the plasma state for much of the implosion. Due to the lack of high-quality data for the submicrosecond regime, the magnetohydrodynamics physics packages of simulation codes (e.g., LASNEX, 13 HYDRA, 14 GORGON 15 ) are not well validated.…”
Section: Introductionmentioning
confidence: 99%
“…We are not entirely sure why this occurs. For liner implosions on much longer time scales (0-6 MA in 7 s), Reinovsky et al [9] also observed suppression of short-wavelength MRT modes, but cite solid-state liner material strength as the reason for this suppression. For the fast liner implosions presented in this Letter, however, simulations using ALEGRA, GORGON, and LASNEX all show that the liner is shock compressed and melted very early in the implosion (prior to any significant motion of the inner liner surface), and thus solid-state material strength is not believed to play a significant role in this fast-implosion case.…”
mentioning
confidence: 99%
“…Imploding z-pinch systems are, however, susceptible to the magneto-Rayleigh-Taylor (MRT) instability [6][7][8][9][10][11][12]. For MagLIF, the loss of liner integrity prior to stagnation could cause the concept to fail.…”
mentioning
confidence: 99%
“…7 This method conserves significant material strength which prevents disruption due to the MRT instability, 8 but the lower implosion velocity-a consequence of the current shaping-may cause significant radiation loss, in addition to allowing instabilities more time to build up. 9 Thus, a tradeoff exists between normal liner implosions and shockless implosions.…”
Section: Introductionmentioning
confidence: 99%